Surgical challenges in the treatment of perimenopausal and postmenopausal endometriosis - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2018)
Endometriosis is classically defined as a chronic, recurrent and progressive disease. It is known to be estrogen-dependent, but can still be observed during the peri- and postmenopausal periods. Medical management of endometriosis is palliative symptomatic relief. Surgery when properly and timely performed for the right person may treat endometriosis. However, there is always a risk of possible major or minor surgical complications, as well as loss of some functions due to nerve damage. Management of endometriosis in the woman approaching the end of her reproductive life may require special attention both due to the potential for recurrence and transformation into various endometriosis-associated malignancies.
Keywords: Endometriosis; surgery; postmenopausal; recurrence; malignant transformation; HORMONE REPLACEMENT THERAPY; BILATERAL SALPINGO-OOPHORECTOMY; OVARIAN-CANCER; MALIGNANT-TRANSFORMATION; CLINICAL CHARACTERISTICS; RECURRENT ENDOMETRIOSIS; ABDOMINAL HYSTERECTOMY; PELVIC ENDOMETRIOSIS; SURGERY; MANAGEMENT